2019
DOI: 10.1016/j.cad.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Parametric design of graded truss lattice structures for enhanced thermal dissipation

Abstract: Truss lattice structures are intricate geometries, whose fabrication has recently been simplified by the development of Additive Manufacturing (AM) technologies. These lightweight geometries present great volume densities and surface-to-occupancy ratios, which makes them ideal for thermal dissipation applications. This paper introduces a new framework for the parametric design of graded truss lattice structures that maximize passive cooling. It exploits the results of a semi-analytic formulation and analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Recently, the SIMP and level set topology optimization approaches have been extended to graded material design problems. Example applications include compliant mechanism design [13], auxetic material design [14], thermal applications [15] and cellular structure design [16]. In this paper, we build on these heterogeneous material topology optimization approaches.…”
Section: Heterogeneous Materials Designmentioning
confidence: 99%
“…Recently, the SIMP and level set topology optimization approaches have been extended to graded material design problems. Example applications include compliant mechanism design [13], auxetic material design [14], thermal applications [15] and cellular structure design [16]. In this paper, we build on these heterogeneous material topology optimization approaches.…”
Section: Heterogeneous Materials Designmentioning
confidence: 99%
“…Yang et al [19] reported that the average Nusselt number of sandwich panel filled with Kagome truss structure is 8% to 37% higher than that filled with tetrahedral truss structure. Vaissier et al [20] proposed a new optimization design method to improve the thermal dissipation capacity of graded truss structures, and the method was validated by several case studies. Hou et al [21] reported that the different arrangement directions of the Kagome-type truss structure in the channel can cause a maximum difference of 9.7% in heat transfer coefficient and 20% in friction coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight porous metals or metal foams have been focused on because of their excellent acoustic, 1) mechanical 2) and thermal 3) properties. Their unique cell structures sometimes cause negative modulus, 4) negative Poisson's ratio 5) and negative stiffness.…”
Section: Introductionmentioning
confidence: 99%